IMPLIKASI SURAT KEPUTUSAN BERSAMA (SKB) TIGA MENTERI 1974 TERHADAP PERKEMBANGAN PENDIDIKAN ISLAM DI INDONESIA - Fuja Sabella; Antika; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2022)
The government's attention to madrasas and Islamic education in general is no less. The establishment of the Ministry of Religion (Depag) on ​​January 3, 1946 is proof of this. There is an education section in its organizational structure whose main responsibility for dealing with issues related to religious education in religious schools (madrasas and Islamic boarding schools) was recognized by the New Order government, then the government adopted a more operational policy in relation to madrasas, namely fostering the quality of madrasah education. In line with these efforts to improve the quality of madrasah education, on March 24, 1975 a policy was issued in the form of a Joint Decree (SKB) of 3 Ministers signed by the Minister of Religion (Prof. Dr. Mukti Ali), Minister of Education and Culture (Lt. Gen. TNI Dr. Teuku Syarif Thayeb) and Minister of Home Affairs (Gen. TNI Retired. Amir Machmud). The purpose of the Three Ministers' Joint Decree is to improve the quality of education in madrasas. With the issuance of the Three Ministerial SKB, madrasas entered a new era, namely the era of equality and equality between madrasas and schools.